THE INFLUENCE OF DISTURBED TONNAGE AND PLAN LINE ON SPENDING DURING THE LINE KEEPING TRACK - Kurgan, M. B.; Chernyshova, O. S. (Science and Transport Progress, 2008)
The research results regarding the change to expenses of materials for the current rail track maintenance are presented.